An exploration of gender-based violence in eastern Myanmar in the context of political transition: findings from a qualitative sexual and reproductive health assessment. Issue 2 (31st May 2019) - Tanabe, Mihoko; Greer, Alison; Leigh, Jennifer; Modi, Payal; Davis, William W.; Mhote, Pue Pue; Htoo, Eh May; Otterness Jr, Conrad M.; Parmar, Parveen
Abstract: In March 2011, the Myanmar Government transitioned to a nominally civilian parliamentary government, resulting in dramatic increases in international investments and tenuous peace in some regions. In March 2015, Community Partners International, the Women's Refugee Commission, and four community-based organisations (CBOs) assessed community-based sexual and reproductive health (SRH) services in eastern Myanmar amidst the changing political contexts in Myanmar and Thailand. The team conducted 12 focus group discussions among women of reproductive age (18–49 years) with children under five and interviewed 12 health workers in Kayin State, Myanmar. In Mae Sot and Chiang Mai, Thailand, the team interviewed 20 representatives of CBOs serving the border regions. Findings are presented through the socioecological lens to explore gender-based violence (GBV) specifically, to examine continued and emerging issues in the context of the political transition. Cited GBV includes ongoing sexual violence/rape by the military and in the community, trafficking, intimate partner violence, and early marriage. Despite the political transition, women continue to be at risk for military sexual violence, are caught in the burgeoning economic push–pull drivers, and experience ongoing restrictive gender norms, with limited access to SRH services. There is much fluidity, along with many connections and interactions among the contributing variables at all levels of the socioecological model; based on a multisectoral response, continued support for innovative, community-based SRH services that include medical and psychosocial care are imperative for ethnic minority women to gain more agency to freely exercise their SR rights.